ANALISIS KINERJA UNIVERSITAS BERSTATUS BADAN LAYANAN UMUM (BLU) (STUDI KASUS PADA UIN SULTAN SYARIF KASIM RIAU) - E r n i t a t i ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2016)
This study aims to determine the performance of UIN Sultan Syarif Kasim Riau as aPublic Service Agency. This study is a qualitative research, that used an interviewas a method to get the data. The findings show that the Performance of UIN SultanSyarif Kasim Riau. While the performance for the University had meet what which isexpected in the Business Strategy Plan 2008-2012. From stakeholder persfektive.Education & leasrning persfektive, human resource and work culture persfektive hadnot achievement the target that already get. Furthermore this study found that fromthe persfektive of financial and administration the Performance of UIN Sultan SyarifKasim Riau.Keywords: performance, balance scorecard.